Bio-physico-chemical Soil Characteristic: Intensive Tillage vs. No Tillage - Ustiatik, Reni; Ariska, Ayu Putri; Ramadhan, Resa Kharisma; Aziz, Novryanti Rizqi; Hadi, Syamsu Ridzal Indra; Nugroho, R Muhammad Yusuf Adi Pujo; Rinandy, Maydella Vista Putri; Hidayat, Muhammad Taufik; Nugroho, Wikan Agung; Kurniawan, Syahrul (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Soil tillage has both positive and negative impacts on soil quality and crop productivity. Efforts to reduce the negative impacts of intensive soil tillage are urgently needed. This study aims to analyze the impact of intensive soil tillage on soil fertility parameters (pH, available P, organic-C, soil compaction, aggregate stability, and soil biodiversity). This research was conducted in two land uses: agriculture and forest land. The research design was descriptive-explorative through surveys and direct field observations. The sample points were determined using stratified random sampling with 3 replications (24 samples). Parameters analyzed in this study were soil compaction, aggregate stability, soil pH, soil available-P, and soil biodiversity (total microbial, soil meso-and-macrofauna). The results showed that intensive tillage affected the soil microbial population, aggregate stability, pH, and available-P (p<0.05). The negative impact of intensive soil tillage reduced total soil microbes by 59.37%. The soil macro and mesofauna found at the study site were earthworms and mycorrhizae, which had a higher density on non-tillage land, with trees as the main vegetation. This encourages efforts to introduce conservation soil tillage to maintain soil biodiversity before more severe damage occurs. Keywords: Intensive agriculture, Soil degradation, Soil fertility, Soil quality, Soil structure.